2016
DOI: 10.4236/psych.2016.74052
|View full text |Cite
|
Sign up to set email alerts
|

Early Reading for Young Deaf and Hard of Hearing Children: Alternative Frameworks

Abstract: Deaf children can develop reading skills by using a visual language to bridge meaning to English print without the use of English auditory phonology. To this end, five deafcentric frameworks are described that take into account the use of visual language and visual learning, as well as the use of deaf cultural role models in the teaching of reading. Moving away from the deficit model, these frameworks focus on Deaf 1 students in the act of reading in order to document their actual behaviors using a bilingual A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 63 publications
(106 reference statements)
0
11
0
2
Order By: Relevance
“…d/Deaf and hard of hearing students who have adequate communication and language skills are more likely to understand the relationship between the through-the-air form of English and its corresponding print form, that is, the fact that spoken sounds correspond with letters or groups of letters [9,53]. Further, these students can obtain sufficient knowledge and skills in areas such as English phonology, vocabulary, and syntax [55].…”
Section: Communication and Language Skillsmentioning
confidence: 99%
“…d/Deaf and hard of hearing students who have adequate communication and language skills are more likely to understand the relationship between the through-the-air form of English and its corresponding print form, that is, the fact that spoken sounds correspond with letters or groups of letters [9,53]. Further, these students can obtain sufficient knowledge and skills in areas such as English phonology, vocabulary, and syntax [55].…”
Section: Communication and Language Skillsmentioning
confidence: 99%
“…Novogrodsky's group also found that deaf children of hearing parents had similar trajectories of ASL development to deaf children of deaf parents, but the skill development was delayed [34]. Based on the outcomes indicating that ASL skills support reading skill development, Andrews and colleagues and Hoffmeister and Caldwell-Harris developed models for alternative pathways to reading skill development based on prior knowledge of ASL for deaf signers [35,36].…”
Section: The Role Of Early Sign Language Development and Emergent Litmentioning
confidence: 99%
“…The focus on auditory phonology is another part of the standard epistemology that impacts how Deaf children are taught to read. Miller and Clark (2011) suggest that this skill is not necessary as well as others who suggest that there are alternative pathways to becoming a skilled Deaf reader (Andrews, Hamilton, Dunn, & Clark, 2016). Greene-Woods and Delgado posit that agreement on how to assess Deaf students allows teachers to pinpoint more effective strategies to determine the true abilities of Deaf readers.…”
Section: Standard Epistemologymentioning
confidence: 99%